Accurate single-tree positions from a harvester: a test of two global satellite-based positioning systems. Issue 8 (17th November 2017) - Hauglin, Marius; Hansen, Endre Hofstad; Næsset, Erik; Busterud, Bjørn Even; Gjevestad, Jon Glenn Omholt; Gobakken, Terje
ABSTRACT: Accurate positioning of single trees registered automatically during harvesting operations opens up new possibilities for reducing the field sampling effort in forest inventories utilising remotely sensed data. In the present study, we propose to use a harvester to collect single-tree data during regular harvest operations and use these data to substitute or supplement traditional measurements on sample plots. Today's harvesters are capable of recording single-tree information such as species and diameter at breast height, and a cut-to-length harvester was equipped with an integrated accurate positioning system based on real-time kinematic global satellite positioning, as well as a low-cost global navigation satellite system (GNSS) receiver mounted directly on the harvester head. Positions from 73 trees were evaluated and compared to coordinates obtained using a total station. At the single-tree level, the mean error for the integrated positioning system was 0.94 m. The low-cost GNSS receiver mounted on the harvester head yielded a mean error of 7.00 m. The sub-meter accuracy obtained with the integrated system suggests that data acquired with a harvester using this positioning system may have a great potential as a method for single-tree field data acquisition.